PERKAWINAN LESBIAN, GAY, BISEKSUAL DAN TRANSGENDER/TRANSEKSUAL (LGBT) PERSPEKTIF HUKUM ISLAM - Rohmawati, R. (IAIN Tulungagung, 2016)
The marriage between transgender, lesbian, gay, bisexual couplehas become the most discussed-public issues. The rising intereston this issue is due to the more open access to the information, freeexpression right, and human rights. In the past, the marriage betweenthose couples was done under cover. Today, such a marriage is not ataboo anymore. The pros and the contras arise. From the perspectiveof Islamic law, the marriage between transgender, lesbian, gay, andbisexual couples is forbidden because it is against the civilized normsof family settlement guided through the transcendental divine of theQuran and Hadis. Such a marriage is a threat to the existence of theessential human nobility because it will devastate human origins,thought, and soul.Kata Kunci: LGBT, Hukum Islam